2016
DOI: 10.1016/j.jad.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural function to happy faces in adolescents with and at risk for depression

Abstract: Background There is accumulating evidence of alterations in neural circuitry underlying the processing of social-affective information in adolescent Major Depressive Disorder (MDD). However the extent to which such alterations are present in youth at risk for mood disorders remains unclear. Method Whole-brain blood oxygenation level-dependent task responses and functional connectivity using generalized psychophysiological interaction (gPPI) analyses to mild and intense happy face stimuli was examined in 29 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 86 publications
0
16
0
Order By: Relevance
“…As such, more advanced pubertal development could contribute to differences in striatal response to reward between high- and low-risk groups. Pubertal development was reported in only four of the nine MDD-risk studies discussed above [50, 58, 67, 68]. Although high-risk offspring tend show earlier pubertal onset in large-scale studies investigating puberty and psychopathology [63], MDD-risk was related to more advanced pubertal development in only one of the studies reviewed here [68].…”
Section: Studying Blunting and Mdd-risk: Developmental Considerationsmentioning
confidence: 97%
See 4 more Smart Citations
“…As such, more advanced pubertal development could contribute to differences in striatal response to reward between high- and low-risk groups. Pubertal development was reported in only four of the nine MDD-risk studies discussed above [50, 58, 67, 68]. Although high-risk offspring tend show earlier pubertal onset in large-scale studies investigating puberty and psychopathology [63], MDD-risk was related to more advanced pubertal development in only one of the studies reviewed here [68].…”
Section: Studying Blunting and Mdd-risk: Developmental Considerationsmentioning
confidence: 97%
“…Two of the MDD-risk studies discussed above also included a currently depressed group to address this issue. Both studies reported similar striatal responses to reward, happy faces [68] or money [51] in healthy high-risk and depressed adolescents. These results suggest that blunted striatal response to reward is not simply a ‘scar’ of MDD, but rather is present to the same degree in never-depressed high-risk groups.…”
Section: Specificity Of Blunted Striatal Responsesmentioning
confidence: 98%
See 3 more Smart Citations